2011
DOI: 10.1051/0004-6361/201116980
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic activity and differential rotation in the very young star KIC 8429280

Abstract: Aims. We present a spectroscopic and photometric analysis of the rapid rotator KIC 8429280, discovered by ourselves as a very young star and observed by the NASA Kepler mission, designed to determine its activity level, spot distribution, and differential rotation. Methods. We use ground-based data, such as high-resolution spectroscopy and multicolor broad-band photometry, to derive stellar parameters (v sin i, spectral type, T eff , log g, and [Fe/H]), and we adopt a spectral subtraction technique to highligh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
73
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 59 publications
7
73
0
Order By: Relevance
“…Lanza et al 2009a). Our spot rotation periods fall within the range found by Frasca et al (2011) for KIC 8429280, while they are close but slightly outside the ranges found for KIC 7765135 and KIC 7985370 by Fröhlich et al (2012). However, those models use seven to nine evolving spots to fit the whole time series instead of two fixed spots applied to fit a data interval.…”
Section: Dr In Our Sample Of Starssupporting
confidence: 68%
“…Lanza et al 2009a). Our spot rotation periods fall within the range found by Frasca et al (2011) for KIC 8429280, while they are close but slightly outside the ranges found for KIC 7765135 and KIC 7985370 by Fröhlich et al (2012). However, those models use seven to nine evolving spots to fit the whole time series instead of two fixed spots applied to fit a data interval.…”
Section: Dr In Our Sample Of Starssupporting
confidence: 68%
“…McQuillan et al (2013) used the stability of the autocorrelation function to point out possible classical pulsators for which low-frequency modes are very stable, but this stability can also be due to longlived active regions or stable groups of starspots at a given active longitude on the star (e.g. Frasca et al 2011;Strassmeier 2009). These long-lived structures, if they are rotating at close rates (due to differential rotation), can produce a beating in the light curve that mimics the effect of activity cycles.…”
Section: Observations and Data Analysismentioning
confidence: 99%
“…In principle, the spot-modeling procedure is as described in Frasca et al (2011) andFröhlich et al (2012). Central to this parameter estimation is the likelihood function.…”
Section: Some General Remarksmentioning
confidence: 99%